2020
DOI: 10.1002/aur.2263
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Developmental and Behavioral Heterogeneity among Preschoolers with ASD: A Cluster Analysis on Principal Components

Abstract: Children with autism spectrum disorder (ASD) present with heterogeneous levels of abilities and deficits. The identification of subgroups within a specific age range could be useful for understanding prognosis and treatment planning. We applied Hierarchical Clustering on Principal Components (HCPC) with a sample of 188 preschoolers with ASD and identified three distinct subgroups based on multiple developmental and behavioral domains. Cluster 1 was characterized by relatively high cognitive, language and adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 51 publications
(74 reference statements)
4
16
0
Order By: Relevance
“…The first one, which represented ∼43% of the sample, underwent great cognitive and adaptive skill improvements (High responders: HR) and the second one, which represented ∼19% of our sample, saw a widening of the gap increased over time compared to typical development in cognition and adaptative behavior (Minimal responders: MR). The clear distinction between toddlers with mild cognitive delay (HB) on one side and others with the more severe cognitive delay at baseline (LF) on the other is very close to results reported by previous studies that applied CA on preschoolers with ASD (52)(53)(54). These studies identified at least two subgroups categorized as high- and low-functioning based on early cross-sectional cognitive measures.…”
Section: Discussionsupporting
confidence: 85%
“…The first one, which represented ∼43% of the sample, underwent great cognitive and adaptive skill improvements (High responders: HR) and the second one, which represented ∼19% of our sample, saw a widening of the gap increased over time compared to typical development in cognition and adaptative behavior (Minimal responders: MR). The clear distinction between toddlers with mild cognitive delay (HB) on one side and others with the more severe cognitive delay at baseline (LF) on the other is very close to results reported by previous studies that applied CA on preschoolers with ASD (52)(53)(54). These studies identified at least two subgroups categorized as high- and low-functioning based on early cross-sectional cognitive measures.…”
Section: Discussionsupporting
confidence: 85%
“…By testing measurement invariance, it is possible to determine whether a factor structure is stable across subgroup membership defined by such variables ( 85 ). Since heterogeneity in ASD and ADHD is influenced by age ( 86 88 ), sex ( 89 91 ), and adaptive functioning ( 92 94 ), these are important variables to consider when examining measurement invariance. It would also be helpful to determine whether the underlying factor structure of ASD and ADHD symptoms is stable across time in the same group of individuals used in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Greater SCI and RRBI corresponded to the most numerous subgroup (56%), whereas fewer participants (10%) made up the subgroup with less SCI and relatively high scores on RRBI. Moreover, based on the levels of RRBI, rather than on the social aspects of autism, Zheng et al [7] reported three subgroups of children with ASD without ID. In parallel, all the subgroups differed on an extended spectrum of clinical behavioral and adaptive measures.…”
Section: Discussionmentioning
confidence: 99%